Haudenosaunee materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950; Fenton, William N., (William Nelson), 1908-2005; Parker, Arthur Caswell, 1881-1955; Newhouse, Seth; Buck, John L.; Séguin, Robert-Lionel; Wallace, Paul A. W.; Ioma, John; Moses, Jesse; Smith, Harlan Ingersoll, 1872-1940; Deardorff, Merle H., 1890-1971; Hill, David (1777)
Materials relating to Speck's study of Haudenosaunee history, language, and culture. Includes correspondence with Haudenosaunee consultants like John L. Buck, Seth Newhouse, Josiah Hill, David S. Hill, etc., on topics ranging from the seizure of wampum by the Canadian government, Newhouse's request that Speck secure wampum for him, Newhouse's offer to sell Speck his history manuscript, which he has been working on since 1885 [#1650], Haudenosaunee burial customs, religion, etc.; an essay by Jesse Moses titled "The Long-House man, a Six Nations Indian of Canada speaks his mind," about the relationship of Christianity and the long-house religion; Speck's correspondence with William N. Fenton, principally concerning field work among the Catawba, Cherokee, and Houma but also touching on Fenton's Seneca field work, Speck's various studies of the Haudenosaunee, and the Second Conference on Iroquois Research; correspondence with other anthropologists about various aspects of Haudenosaunee history and culture such as material culture specimens, archaeology, historical sources, agriculture, education, warfare, religion, population statistics, etc.; a draft of Speck's "Reflections on Iroquois religion" and related correspondence; an undated document describing a meeting of Delaware, Nanticoke, and Canadian Iroquois in the presence of Speck and recounting the injustices suffered by Indians in United States and Canada; a copy of a 1777 treaty made by Peter F. Timothy, a Moravian Delaware, in August 1888, and transmitted to Speck by Jesse Moses; and Speck's research notes and other miscellaneous correspondence on topics such as masks, art, museum specimens, hunting territory, chiefships, words, warfare with the Abenaki, the Delaware-as-women theme, academic publications and conferences, etc.